1995
DOI: 10.1038/373623a0
|View full text |Cite
|
Sign up to set email alerts
|

Axl receptor tyrosine kinase stimulated by the vitamin K-dependent protein encoded by growth-arrest-specific gene 6

Abstract: The Axl receptor tyrosine kinase was identified as a protein encoded by a transforming gene from primary human myeloid leukaemia cells by DNA-mediated transformation of NIH 3T3 cells. Axl is the founding member of a family of related receptors that includes Eyk, encoded by a chicken proto-oncogene originally described as a retroviral transforming gene, and c-Mer, encoded by a human proto-oncogene expressed in neoplastic B- and T-cell lines. The transforming activity of Axl demonstrates that the receptor can dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
372
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(381 citation statements)
references
References 12 publications
8
372
0
1
Order By: Relevance
“…Members of this family display IgG-like and fibronectin type III domains in their extracellular domain, features reminiscent of cell adhesion molecules; indeed, we were able to demonstrate that the ARK receptor can behave like a cell adhesion molecule by inducing cell aggregation through a homophelic mechanism (Bellosta et al, 1995). Recently Gas6 was identi®ed as a heterophilic ligand for ARK and Tyro3 receptors and c-mer, while Protein S was identi®ed as the ligand for the Tyro3 receptor (Nagata et al, 1996;Mark et al, 1996;Stitt et al, 1995;Varnum et al, 1995). Both proteins belong to the class of vitamin K dependent proteins but while Protein S is involved in the anticoagulation cascade (Dahlback, 1991), Gas6 was originally isolated as a Growth Arrest Speci®c gene from quiescent ®broblasts (Man®oletti et al, 1993).…”
Section: Introductionmentioning
confidence: 75%
“…Members of this family display IgG-like and fibronectin type III domains in their extracellular domain, features reminiscent of cell adhesion molecules; indeed, we were able to demonstrate that the ARK receptor can behave like a cell adhesion molecule by inducing cell aggregation through a homophelic mechanism (Bellosta et al, 1995). Recently Gas6 was identi®ed as a heterophilic ligand for ARK and Tyro3 receptors and c-mer, while Protein S was identi®ed as the ligand for the Tyro3 receptor (Nagata et al, 1996;Mark et al, 1996;Stitt et al, 1995;Varnum et al, 1995). Both proteins belong to the class of vitamin K dependent proteins but while Protein S is involved in the anticoagulation cascade (Dahlback, 1991), Gas6 was originally isolated as a Growth Arrest Speci®c gene from quiescent ®broblasts (Man®oletti et al, 1993).…”
Section: Introductionmentioning
confidence: 75%
“…Recently, several studies have indicated that K vitamins are involved in processes other than blood coagulation and include growth control and differentiation (Akedo et al, 1992;Manfioletti et al, 1993;Stitt et al, 1995;Varnum et al, 1995;Crossier et al, 1996;Saxena et al, 1997;Yaguchi et al, 1997). These include:…”
Section: Initial Observations In Vitro and In Vivomentioning
confidence: 99%
“…(1) gas 6, the growth arrest-specific gene product, is carboxylated with vitamin K as a cofactor and binds to a growth-regulatory receptor, Axl (Varnum et al, 1995). (2) Two receptor tyrosine kinases (RTKs) involved in hematopoietic differentiation (Dkt and Ufo) employ vitamin K-carboxylated proteins as their ligands (Stitt et al, 1995;Crossier et al, 1996).…”
Section: Initial Observations In Vitro and In Vivomentioning
confidence: 99%
“…AXL (also known as UFO/ARK/Tyro) is a RTK with oncogenic potential and transforming activity (Wimmel et al, 2001), which is stimulated by its ligand GAS6 (growth arrest-specific 6), a vitamin K-dependent growth potentiating factor (Varnum et al, 1995). AXL was first identified as a transforming gene in chronic myeloid leukemia (Janssen et al, 1991;O'Bryan et al, 1991), but is also overexpressed in metastatic colon and prostate cancer, thyroid carcinoma, breast cancer and melanoma (Quong et al, 1994;Craven et al, 1995;Ito et al, 1999;Jacob et al, 1999;Meric et al, 2002).…”
Section: Introductionmentioning
confidence: 99%